Efficacy of preoperative amino acid supplements on postoperative physical function and complications in open heart surgery patients: A study protocol for a randomized controlled trial. Issue 4 (October 2019) - Ogawa, Masato; Yoshida, Naofumi; Satomi-Kobayashi, Seimi; Tsuboi, Yasunori; Komaki, Kodai; Wakida, Kumiko; Gotake, Yasuko; Inoue, Takeshi; Tanaka, Hiroshi; Yamashita, Tomoya; Sakai, Yoshitada; Izawa, Kazuhiro P.; et al.
Highlights: This is a single-center randomized trial. We will evaluate clinical efficacy of preoperative amino acid supplements. The main outcome will be a change in the 6-min walking test distance. This trial could propose a preoperative management in open heart surgery patients. Abstract: Background: Elderly patients undergoing cardiac surgery often show poor nutritional status, muscle wasting, and sarcopenia, which are reported to affect postoperative functional recovery and incidence of complications. Amino acids are essential in maintaining nutritional status, synthesizing muscle protein, and promoting beneficial energy balance of the heart muscle. β-Hydroxy β-methylbutyric acid (HMB) is a leucine metabolite known to increase muscle protein synthesis and inhibit protein catabolism; it has been used to more effectively support patients with muscle wasting due to wearing diseases. However, the efficacy of amino acid administration comprising HMB in patients undergoing open heart surgery remains unclear. This study aims to examine whether preoperative short-term aggressive amino acid administration helps support postoperative recovery of physical function and prevent complications. Methods: This is a single-center prospective randomized controlled trial (UMIN000030490). Patients aged ≥65 years who will be hospitalized for medical examination before cardiac surgery will be recruited. The participants will be randomly assigned to the experimental or control group. The experimental group will be administered with an amino acid supplement with HMB 1200 mg, l -glutamine 7000 mg, andl -arginine 7000 mg once or twice per day depending on the degree of renal dysfunction, for 14–28 days preoperatively. The control group will not receive any nutritional intervention. The main outcome will be a change in the 6-min walking test distance pre- and postoperatively as a sign of functional recovery. Secondary outcomes such as the incidence of complications; physical, nutritional, and psychological states; mortality; and length of hospital stay will also be evaluated. Conclusion: This clinical study will determine the effects of preoperative short-term oral amino acid supplementation with HMB, l -glutamine, andl -arginine on postoperative physical function in elderly patients undergoing cardiac surgery.